DETERMINATION OF DRAG COEFFICIENT IN PROJECTILE MOTION USING LINEAR DRAG - ADNAN WIJAYA (NIM : 90215001), PRADITA
Experimental tool design has been conducted to analyze projectile motion affected by drag. The experiment conducted by analyzing the video of projectile motion launched by the experimental tool using Tracker software and compared the result with numerical simulation using VBA in Microsoft Excel. Curve fitting method was used to compared both data. The result of projectile motion analysis using different mass and shape of the projectile shows that mass and shape of the projectile affect the value of initial velocity (v0), drag, and range of the projectile motion. Projectile with smallest mass (60 gr) not only has the most stable initial velocity (v0) and drag, but also farthest range.